Respon Emosional Pasien dan Keluarga dalam Visit Pasien pada Layanan Bina Rohani di Rumah Sakit - Syahla Mahddiyah; Imam Alfi (Da'wah Faculty of UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
Spiritual development services are provided to provide spiritual support for patients undergoing medical treatment, as the sick condition often causes anxiety, fear, and psychological distress. The support of this spiritual guidance service is expected to help patients feel calmer, increase their hope of recovery, and strengthen mental resilience during the treatment process. This study aims to explore the emotional response of patients and families to patient visit services in Islamic spiritual guidance at PKU Muhammadiyah Petanahan Kebumen Hospital. This research method employs a qualitative approach, utilizing data collection techniques that include observation, in-depth interviews with spiritual development officers, and documentation. The data produced was then analyzed. The results showed that patients' emotional responses after receiving spiritual guidance varied, ranging from feelings of calmness and increased hope for healing to emotional release, as evidenced by expressions of gratitude. These findings indicate that spiritual guidance helps patients manage anxiety, fear, and psychological distress during treatment. In addition, the patient's family also benefited from this service, with most feeling calmer and obtaining the emotional support they needed. This research confirms the importance of integrating spiritual services into medical care to enhance the emotional well-being of patients and their families. Layanan bina rohani diberikan untuk memberikan dukungan spiritual bagi pasien yang menjalani perawatan medis, karena kondisi sakit sering menimbulkan kecemasan, ketakutan, dan tekanan psikologis. Dukungan layanan bimbingan rohani ini diharapkan membantu pasien supaya merasa lebih tenang, meningkatkan harapan sembuh, serta memperkuat ketahanan mental selama proses pengobatan. Penelitian ini bertujuan mengeksplorasi respon emosional pasien dan keluarga pada layanan visit pasien pada bimbingan rohani Islam di Rumah Sakit PKU Muhammadiyah Petanahan Kebumen. Metode penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui observasi, wawancara mendalam kepada petugas bina rohani, dan dokumentasi. Data yang dihasilkan kemudian dilakukan analisis data. Hasil penelitian menunjukkan bahwa respon emosional pasien setelah menerima bimbingan rohani bervariasi, mulai dari perasaan lebih tenang, harapan sembuh yang meningkat, hingga pelepasan emosi yang tampak melalui ungkapan syukur. Temuan ini mengindikasikan bahwa bimbingan rohani membantu pasien mengelola kecemasan, ketakutan, dan tekanan psikologis selama perawatan. Selain itu, keluarga pasien juga merasakan manfaat layanan ini, dengan sebagian besar merasa lebih tenang dan memperoleh dukungan emosional yang dibutuhkan. Penelitian ini menegaskan pentingnya integrasi layanan spiritual dalam perawatan medis untuk meningkatkan kesejahteraan emosional pasien dan keluarga.